Respuesta :

ANSWER

[tex](1-7x)(1+9x) =- 63 {x}^{2} + 2x + 1[/tex]

EXPLANATION

The given product is (1-7x)(1+9x).

Expand using the distributive property.

[tex](1-7x)(1+9x) = 1(1 + 9x) - 7x(1 + 9x)[/tex]

[tex](1-7x)(1+9x) = 1 + 9x - 7x - 63 {x}^{2}[/tex]

Simplify to obtain:

[tex](1-7x)(1+9x) = 1 + 2x - 63 {x}^{2}[/tex]

You can rewrite in standard form to get,

[tex](1-7x)(1+9x) =- 63 {x}^{2} + 2x + 1[/tex]

Answer:

1+2x-63x^2

Step-by-step explanation:

factor 1(1+9x)=1+9X

-7x(1+9x)=-7x-63x^2

add 1+9x-7x-63x2